STRATEGI INDONESIA DALAM MENINGKATKAN DAYA SAING EKSPOR KOMODITI MINYAK ATSIRI KE AMERIKA SERIKAT - Santika Putri; Umi Oktyari Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to explain the opportunities and challenges of exporting Indonesian essential oil commodities to the United States. In this study using secondary qualitative research methods. Liberalists have the view that international cooperation is carried out on the basis of long-term reciprocal interests and benefits, meaning that international cooperation carried out by Indonesia and the United States aims to meet the needs of both countries. Indonesia is a country that produces essential oils which are raw materials for products that produce fragrances such as perfume. It is hoped that the cooperation between Indonesia and the United States will produce at least three mutual benefits as follows (1) the fulfillment of the interests of each country, (2). Generate cooperation that is able to exchange benefits and (3). There is knowledge about the development of essential oils as downstream products for Indonesia. Keywords: Export, international cooperation, essential oil